The strategic development of multinationals : subsidiaries and innovation - Papanastassiou, Marina, 1965-; Pearce, Robert D., 1943- (Palgrave Macmillan, 2009)
"Globalization is a "buzz-word" for the twenty-first century, but this volume argues that it is not possible to understand the current global economy without understanding the multinational"--Resumé vydavatele
Keywords: nadnárodní společnosti; mezinárodní podnikání; strategický management; international business enterprises; international business; strategic planning; studie; studies